Conversações latino-americanas com Débora Maria da Silva (Movimento Independente Mães de Maio, Brasil) - Bonvillani , Andrea; Souza, Caroline Matias de; Silva, Débora Maria da; Galindo, Liliana; Vergueiro, Alice; Botero-Gómez, Patricia; Alves Oliveira , Rita de Cássia (Ponto-e-Vírgula, 2022)
.